Performance Analysis of Atmospheric Turbulence Mitigation Techniques for Free Space Optical Communication - Sharma, Ajay (My University, 2017)
The gigabit rate operated free space optical (FSO) link has been designed for inter-building or campus connectivity. The atmospheric losses have the major drawback in FSO, mainly because of fog scintillation and precipitation. The impact of fog, rain and snow on FSO has been investigated and analyze their performances for optical wireless system. Hybrid FSO/RF system with 1550 nm/2.4 GHz link has also been studied to provide uninterrupted communication in any atmospheric condition of heavy fog and rain. The model of FSO system has been studied with the help of MATLAB simulator using simulink where channel considered as free space. In this model, Additive White Gaussian Noise (AWGN) channel has considered to analyses bit error rate (BER) and power of FSO signal. The consequence of atmospheric turbulence of free space on transmitted signal has examined. The BER as well as signal power has extremely ruined on rigorous atmospheric unstable condition even for a short distance in optical wireless channel. The bit error rate of less than 10-3 has been achieved for free space optical communication system which has been considered being excellent. The propagation of Gaussian beam in turbulent atmosphere for free space optical communication has been studied. The intensity on axis of Gaussian beam wave, beam radius and radius of curvature at the receiver has been evaluated and discussed. The effect of aperture averaging on Gaussian beam wave for different turbulence strength of atmosphere has been studied. The aperture averaging factor decreases under high atmospheric strength and averaging ability of the receiving system increases by increasing receiving aperture diameter. Additionally an improved expression of scintillation loss has been evaluated using threshold power approach. This expression takes into account the loss due to scintillation when Gaussian wave propagates through atmospheric turbulence condition. Results show that probability of fading and losses due to scintillation are considerably lower when threshold power level has been set low. The varying weather conditions have a major influence on the performance of FSO transmission. This is investigation based on the effects of different weather circumstances on data rate, received signal and S/N ratio at 1550 nm/ 1300 nm/ 850 nm wavelength for a free space optical communication. The system performance improved in different weather condition by Fresnel lens techniques such as data rate, received power and S/N ratio. By using this technique, non coherent light source such as LED has been used instead of LASER in free space optical communication. The potential of LEDs to be modulated at high speeds offers the possibility of using LED as sources for communication instead of LASER. Simulation results shows that heavy fog attenuates more optical signal then other atmospheric condition and in all weather conditions.
Keywords: free space optics; Radio Frequency; Vertical Cavity Surface Emitting Diode; Dense Wave Division Multiplexing